Brachytherapy in the treatment of bile duct cancer – a tough challenge - Skowronek, Janusz; Zwierzchowski, Grzegorz (Journal of Contemporary Brachytherapy, 2017)
The majority of patients with bile duct cancer are diagnosed with clinically advanced disease. Most of these patients have a short life expectancy and are treated with palliative aim. Most patients present with locally advanced or metastatic disease, which is not amenable to surgical resection, resulting in poor survival. Adjuvant or definitive radiotherapy, with or without chemotherapy, is therefore used in many centers worldwide for better local control, and with the expectation that it will have a favorable effect on survival. However, the lack of appropriate prospective trials, as well as the small size of the published series and their retrospective nature, has produced insufficient evidence for the best treatment for these patients. Intraluminal brachytherapy is an important component in the multimodality approach to bile duct cancers. The objective of this treatment is to deliver a high local dose of radiation to the tumor while sparing surrounding healthy tissues. The treatment can be safely adapted for right and left hepatic duct, and for common bile duct lesions. Brachytherapy plays a limited but specific role in definitive treatment with curative intent in selected cases of early disease, as well as in the postoperative treatment of small residual disease. Depending on the location of the lesion, in some cases, brachytherapy is a treatment of choice. Clinical indications, different techniques, results, and complications are discussed in this work.